Engineering earth the impacts of megaengineering projects - Brunn, Stanley D.; SpringerLink (Online service). (Dordrecht Springer Netherlands, 2011)
A pioneering volume that documents and illustrates the scale and impacts of many megaprojects. This is the first book to examine the actual impact of physical and social engineering projects in more than fifty countries from a multidisciplinary perspective. The book brings together an international team of nearly two hundred authors from over two dozen different countries and more than a dozen different social, environmental, and engineering sciences. Together they document and illustrate with case studies, maps and photographs the scale and impacts of many megaprojects and the importance of studying these projects in historical, contemporary and postmodern perspectives. This pioneering book will stimulate interest in examining a variety of both social and physical engineering projects at local, regional, and global scales and from disciplinary and trans-disciplinary perspectives.
I: Introduction.- II: GIS, ICT's and K-Economies.- III:Agriculture, Fishing and Mining Projects.- IV: Energy and Industrial Projects.- V: Transportation Projects.- VI: Construction Companies and Corporation Strategies.- VII: Megafacilities, Designs and Architecture.- VIII: Tourism, Recreation and Amenity Landscapes.- IX: Reconstructing and Restoring Nature.- X: River Diversion and Coastal Reclamation Projects.- XI: Dams.- XII: Military, Security, and Risk Landscapes.- XIII: Sociallly Engineered Landscapes.- XIV: Political Organization of Space.- XV: Earth and Planetary Engineering
Electronic reproduction.
Keywords: Engineering; Engineering -- Data processing; Electronic books